HPA axis dysregulation in adult adoptees twenty years after severe institutional deprivation in childhood. (December 2017) - Kumsta, Robert; Schlotz, Wolff; Golm, Dennis; Moser, Dirk; Kennedy, Mark; Knights, Nicky; Kreppner, Jana; Maughan, Barbara; Rutter, Michael; Sonuga-Barke, Edmund
Highlights: Adverse childhood experiences are associated with HPA axis dysregulation. We investigated a sample where specific timing and duration of adversity is known. Extended childhood deprivation is associated with a lack of the cortisol awakening response. Shorter duration of deprivation is associated with an attenuated CAR. Abstract: Hypothalamic–pituitary–adrenal (HPA) axis function is disrupted in institutionally-deprived children – reduced morning cortisol, flattened diurnal slope and blunted reactivity persist even after successful adoption into positive family environments. Here we test whether such effects persist into adulthood. Cortisol release across the day (sampled at awakening, 30 and 45 min later, and at four points across the day) was investigated in young adult adoptees who had lived in severe deprivation for up to 43 months in early childhood in Ceaușescu's Romanian orphanages and a comparison group of non-deprived UK adoptees (Total N = 57; mean age = 24 ± 0.9 years). The mediating role of cortisol levels on adult mental health was examined using data from standardized clinical assessments. Cortisol profiles were disrupted in the Romanian adoptees who experienced more than 6 months deprivation marked by a striking absence of the cortisol awakening response (CAR) and a significantly flatter cortisol curve until 1 h 15 min after awakening. Whereas institutional deprivation was associated with both cortisol secretion and emergence of emotional problems in young adulthood, path analysis revealed no evidence for a mediating role of CAR disruption in the sub-sample studied here. The results are in line with findings of HPA axis hypo-functionality following early adverse experience and provide strong evidence for long-term programming effects of HPA axis function through experience of institutional deprivation.